1972
DOI: 10.1902/jop.1972.43.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Crest Reduction Following Full and Partial Thickness Flaps

Abstract: THE POSSIBILITY THAT periodontal surgical procedures may result in loss of alveolar support has been of special concern to clinicians since the findings of Wilderman. 1 This concern has resulted in modifications of surgical techniques to provide more protection for the alveolar bone. One such modification has been the maintenance of a connective tissue layer over the alveolar bone. 2,3,4 The present clinical study evaluated the differences in the response of the marginal radicular bone to the full thickness mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
189
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 6 publications
11
189
0
9
Order By: Relevance
“…Performing a standalone flap surgery for a 25-31% increase in the rate of tooth movement requires careful consideration because flap elevation can produce alveolar bone loss. 81,93,94 However, if surgery is being performed for other purposes, the benefit of the increased rate of tooth movement due to flap elevation should be considered. For example, in cases of premolar extraction, the clinician might choose to elevate a flap at the time of extraction if orthodontic treatment is being initiated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…Performing a standalone flap surgery for a 25-31% increase in the rate of tooth movement requires careful consideration because flap elevation can produce alveolar bone loss. 81,93,94 However, if surgery is being performed for other purposes, the benefit of the increased rate of tooth movement due to flap elevation should be considered. For example, in cases of premolar extraction, the clinician might choose to elevate a flap at the time of extraction if orthodontic treatment is being initiated immediately.…”
Section: Discussionmentioning
confidence: 99%
“…In the case reports presented above, a minimally invasive flap was created to expose the surgical site and the root fragment during the subsequent implantation procedure (re-entry). To prevent further compromise of the blood supply to the vestibular bone, relief incisions were kept to a minimum [29]. Complete preservation of the buccal lamellar bone was observed intra-operatively in all three cases.…”
Section: Discussionmentioning
confidence: 99%
“…Since the alveolar bone resorption continues throughout life (Jahangiri et al, 1998), the longer the interval, the greater will be the amount of bone resorption. In addition, it was well established that the elevation of a full-thickness flap might cause crestal alveolar bone loss of about 0.6 mm (Wood et al, 1972), making tooth extraction no longer the sole factor causing alveolar bone resorption (Fickl et al, 2008). This might partially be the reason why studies using the method of flap elevation (Lekovic et al, 1998;Camargo et al, 2000) reported more resorption.…”
Section: Resultsmentioning
confidence: 99%